Report on a novel emerging class of highly potent benzimidazole NPS opioids: Chemical and in vitro functional characterization of isotonitazene. Issue 4 (8th January 2020) - Blanckaert, Peter; Cannaert, Annelies; Van Uytfanghe, Katleen; Hulpia, Fabian; Deconinck, Eric; Van Calenbergh, Serge; Stove, Christophe
Abstract: This paper reports on the identification and full chemical characterization of isotonitazene ( N, N ‐diethyl‐2‐[5‐nitro‐2‐({4‐[(propan‐2‐yl)oxy]phenyl}methyl)‐1H‐benzimidazol‐1‐yl]ethan‐1‐amine), a potent NPS opioid and the first member of the benzimidazole class of compounds to be available on online markets. Interestingly, this compound was sold under the name etonitazene, a structural analog. Identification of isotonitazene was performed by gas chromatography mass spectrometry (GC–MS) and liquid chromatography time‐of‐flight mass spectrometry (LC‐QTOF‐MS), the latter identifying an exact‐mass m/z value of 411.2398. All chromatographic data indicated the presence of a single, highly pure compound. Confirmation of the specific benzimidazole regio‐isomer was performed using 1 H and 13 C NMR spectroscopy, after which the chemical characterization was finalized by recording Fourier‐transform (FT‐IR) spectra. A live cell‐based reporter assay to assess the in vitro biological activity at the μ‐opioid receptor (MOR) revealed that isotonitazene has a high potency (EC50 of 11.1 nM) and efficacy (Emax 180% of that of hydromorphone), thus confirming that this substance is a strong opioid. Isotonitazene has not been previously detected, either in powder form, or in biological fluids. The high potency and efficacy of isotonitazene, combined with the fact that this compound was being sold undiluted, represents an imminent danger to anyone aiming to use this powder. Abstract : The identification and full chemical characterization of isotonitazene, a potent NPS opioid: the first member of the benzimidazole class to be available on online markets; a confirmed high potency and efficacy (in vitro); sold under wrong name 'etonitazene'.